Isolated Components From Spider Venom Targeting Human Glioblastoma Cells and Its Potential Combined Therapy With Rapamycin - Caballero, Marcus; Barreto, Natalia; Bonfanti, Amanda Pires; Munhoz, Jaqueline; Rocha e Silva, Thomaz; Sutti, Rafael; Verinaud, Liana; Pinheiro de Mato, Felipe Cezar; Lanfredi, Guilherme Pauperio; Rapôso, Catarina (Frontiers in Molecular Biosciences, 2022)
Glioblastomas (GBs) are responsible for a higher mortality rate among gliomas, corresponding to more than 50% of them and representing a challenge in terms of therapy and prognosis. Peptide-based antineoplastic therapy is a vast and promising field and these molecules are one of the main classes present in spider venoms. Recently, our research group demonstrated cytotoxic effects of Phoneutria nigriventer spider venom (PnV) in GB. The present study aims to select the purified PnV-components with potential antineoplastic effects, as well as to compare different metabolic conditions. Human GB (NG97) cells were treated with the PnV fractions: F1 (less than 3 kDa), F2 (between 3 and 10 kDa) and F3 (greater than 10 kDa). After treatment, viability (MTT), proliferation (CFSE), death (Annexin V/propidium iodide - PI), cell cycle (PI) and protein expression via western blotting (for BCL-2 and BAX) were performed. The F1 and F2 fractions showed more relevant effects and were repurified in subfractions (SF1 - SF11); from these, SF3 and SF4 showed the most significant effects. The previous inhibition of mTOR by rapamycin had a synergistic effect with SFs, reducing cell viability even more significantly compared to untreated control. The BAX protein, related to the induction of apoptosis, was increased by SF3 and BCL-2, related to anti-apoptotic mechanisms, was reduced by SF3 and SF4. Both proteins were even more altered when mTOR was inhibited, corroborating the synergistic effect of the drugs. Taken together, the results point to components present in SF3 and SF4 as potential prototypes for the development of new drugs for GB treatment and stimulate studies to use these compounds in combination therapy with rapamycin-like activity. Future studies will be conducted to characterize, synthesize the molecules and to evaluate the efficacy and safety in pre-clinical models.